2a+3(a-7)=a+3

Simple and best practice solution for 2a+3(a-7)=a+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+3(a-7)=a+3 equation:


Simplifying
2a + 3(a + -7) = a + 3

Reorder the terms:
2a + 3(-7 + a) = a + 3
2a + (-7 * 3 + a * 3) = a + 3
2a + (-21 + 3a) = a + 3

Reorder the terms:
-21 + 2a + 3a = a + 3

Combine like terms: 2a + 3a = 5a
-21 + 5a = a + 3

Reorder the terms:
-21 + 5a = 3 + a

Solving
-21 + 5a = 3 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
-21 + 5a + -1a = 3 + a + -1a

Combine like terms: 5a + -1a = 4a
-21 + 4a = 3 + a + -1a

Combine like terms: a + -1a = 0
-21 + 4a = 3 + 0
-21 + 4a = 3

Add '21' to each side of the equation.
-21 + 21 + 4a = 3 + 21

Combine like terms: -21 + 21 = 0
0 + 4a = 3 + 21
4a = 3 + 21

Combine like terms: 3 + 21 = 24
4a = 24

Divide each side by '4'.
a = 6

Simplifying
a = 6

See similar equations:

| 4(2x-5)=3(8-x) | | 4w+6x-13y+5w+7x+7y= | | 10n+7=107 | | 16a+17b+2c+2c-4b-3a= | | 2i+7=5i-2 | | 11p+19q+p-3q-6p= | | 3(2x-5)=27 | | x+(x+6)+12=66 | | 71-2x=34x+23 | | 14m+6n-4m+7n= | | (x+6)+12=66 | | 14-7x=110-35x | | 6a+1=2a+25 | | X^2-71*x+72=0 | | 2x+3=19+x | | -26-7x=110-35x | | -3x^2=-12 | | 180-7x=20x+21 | | 9t-3=8t-18 | | 7y+3=12y+8 | | -155-7x=10x+15 | | -155-7x=10x+25 | | 18+4y=18 | | 8x^2+3x+10=0 | | 6n-7=3n+2 | | 5x-18=22 | | 3x+7x=8 | | 3n+6=n+10 | | 7x^2-6x-111=0 | | 4.4x+3.8=13.2 | | 4x+34=12x-38 | | 4*0.5-3y=11 |

Equations solver categories